Label-Free Biosensing Advanced Materials, Devices and Applications - Schöning, Michael J.; Poghossian, Arshak; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume summarizes the state-of-the-art technologies, key advances and future trends in the field of label-free biosensing. It provides detailed insights into the different types of solid-state, label-free biosensors, their underlying transducer principles, advanced materials utilized, device-fabrication techniques and various applications. The book offers graduate students, academic researchers, and industry professionals a comprehensive source of information on all facets of label-free biosensing and the future trends in this flourishing field. Highlights of the subjects covered include label-free biosensing with: · semiconductor field-effect devices such as nanomaterial-modified capacitive electrolyte-insulator-semiconductor structures, silicon nanowire transistors, III-nitride semiconductor devices and light-addressable potentiometric sensors · impedimetric biosensors using planar and 3D electrodes · nanocavity and solid-state nanopore devices · carbon nanotube and graphene/graphene oxide biosensors · electrochemical biosensors using molecularly imprinted polymers · biomimetic sensors based on acoustic signal transduction · enzyme logic systems and digital biosensors based on the biocomputing concept · heat-transfer as a novel transducer principle · ultrasensitive surface plasmon resonance biosensors · magnetic biosensors and magnetic imaging devices .
Nanomaterial-modified Capacitive Field-effect Biosensors -- Silicon Nanowire Field-effect Biosensors -- Label-free Biosensors Based on III-Nitride Semiconductors -- (Bio-)chemical Sensing and Imaging by LAPS and SPIM -- Biosensorial Application of Impedance Spectroscopy with Focus on DNA Detection -- Label-free Impedimetric Biosensing Using 3D Interdigitated Electrodes -- Electrochemical Nanocavity Devices -- Computational Modeling of Biomolecule Sensing with a Solid-state Membrane -- Amperometric Sensors Based on Carbon Nanotubes in Layer-by-Layer Films -- Graphene-based Biosensors and their Applications in Biomedical and Environmental Monitoring -- Label-free MIP-Sensors for Protein Biomarkers -- Biomimetic Recognition for Acoustic Sensing in Liquids -- Enzyme Logic Systems - Biomedical and Forensic Biosensor Applications -- Heat Transfer as a New Sensing Technique for the Label-Fee Detection of Biomolecules -- Towards Ultrasensitive Surface Plasmon Resonance Sensors -- Biomagnetic Sensing.
Keywords: Nanochemistry; Microtechnology; Microelectromechanical systems; Nanotechnology; Biotechnology; Biophysics; Biology -- Technique; Nanochemistry; Microsystems and MEMS; Nanotechnology; Biotechnology; Biophysics; Biological Techniques